Investigating the Effects of Acupuncture on Autism Through Varying and Combined Methods - K. Cheng, Fung (Current Traditional Medicine, 2017)
Background: Autism spectrum disorders pertain to neuro-developmental disorders that threaten not only the quality of life and social activities of children (or adults) with these illnesses in their lifetime if no proper training is provided, but also multiplies social costs such as public health expenditures. A variety of treatments, including complementary and alternative medicine, demonstrate improvement, among which acupuncture shows impacts on the autistic symptoms. Method: This literature review includes 37 empirical projects with 2,743 children in mainland China, Hong Kong, the UK, and Egypt. It offers an overview of the effectiveness of acupuncture, a traditional Chinese medical practice, on enhancing impairments that affect these disorders; for example, communication and social skills, sensation, speech, motor skills, behaviour, emotion, cognition, intelligence, and self-care. Performed in different forms (for example, scalp and tongue acupuncture, auricular point pressure), this method can be used alone or with other therapies, supported by advanced technology such as electroacupuncture and laser acupuncture. Result: Although the findings are encouraging, well-designed randomised controlled studies are suggested for further research. Conclusion: In summary, acupuncture is a potential measure for treating autism.
Keywords: literature review